Influence Profitability, Solvency, Quality Auditor and Audit Tenure against Audit Delay in Sub-Sector Manufacturing Companies Metals Listed on the Indonesia Stock Exchange - Arie Pratania Putri; Rekha Liza Simanjuntak; Indah Permata Sari Br Sembiring (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of profitability, solvency, auditor quality, audit tenure on audit delay. In addition, analyzing asset management called ROA (Return On Assets), estimates the company's expertise in taking advantage of investor speculation from the company's ROE (Return On Equity) and also the company uses the speculative expertise of investors and considers the company's expertise to handle debt and company obligations. DER (Debt to Equity Ratio) will audit delay. The object of this research is a manufacturing company in the metal sub-sector that is included in the IDX (Indonesian Stock Exchange) in the 2017-2019 period. Through the use of purposive sampling technique, the research sample was 46 companies. The analysis was carried out using non-probability sampling. The results of this study show that profitability with ROA (Return On Assets) as a benchmark, profitability with ROE (Return On Equity) as a benchmark, solvency with a DER (Debt to Equity Ratio) benchmark, auditor quality and audit tenure have a negative effect on audit delay. Profitability using ROA (Return On Assets), profitability using ROE (Return On Equity), solvency by measuring DER (Debt to Equity Ratio), auditor quality and audit tenure simultaneously affect audit delay for manufacturing companies in the metal sub-sector listed on the IDX (Indonesian Stock Exchange) in the 2017-2019 period.